Vegitable Breeding principles and Practices - Hari Har Ram; Hari Har Ram (Ludhiana Kalyani, 1998)
This book present the basic principles of plant breeding, biotechnology and application of plant breeding and plant biotechnology to vegitable improvement in india.
Introductory Topics Basic Concepts Breedin Of Vegitable Crops
Keywords: Introductory Topics, Basic Concepts, Breedin Of Vegitable Crops